Fractal signature analysis measures cancellous bone organisation in macroradiographs of patients with knee osteoarthritis. Issue 10 (October 1996) - Buckland-Wright, J C; Lynch, J A; Macfarlane, D G
Abstract : OBJECTIVE: To determine whether fractal signature analysis (FSA) of digitised macroradiographs of knees quantifies alterations in trabecular structure in the tibial cancellous bone of osteoarthritic patients with either early or definite joint space narrowing compared with non-arthritic subjects. METHODS: 90 osteoarthritic knees had macroradiographs at x5 magnification. Joint space width and FSA of horizontal and vertical trabecular organisation in the tibial subarticular cancellous bone were measured in the medial and lateral tibio-femoral compartments and compared to reference values obtained from the knees of 14 healthy non-arthritic volunteers, and to the subject's age and weight. RESULTS: Compared to the non-arthritic joints, FSA of the trabecular structure of the medial diseased compartment of the tibia was significantly different and correlated with the degree of joint space narrowing (P < 0.003); FSA of horizontal trabecular structures decreased (P < 0.001) in knees with early osteoarthritis (joint space > 3 mm) and vertical trabecular FSA increased in knees with marked joint space narrowing (joint space < 3 mm). In the lateral compartment of the tibia, FSA did not show a difference between any of the categories. With increasing age of all subjects, the changes in FSA indicated a significant increase in the number of fine horizontal and vertical trabeculae. No correlation was found between the subjects' body weight and changes in the subarticular cancellous bone organisation. CONCLUSIONS: FSA quantifies changes in cancellous bone organisation in knee osteoarthritis. In the diseased compartment, increased horizontal trabecular thickness occurred early and preceded the later changes in the vertical structures.